Exploring factors influencing ethical marketing of biomedical products: A case study in Pakistan - Wu, Huizhi; Wang, Wei; Hussain, Talib; Rehman, Manzar; Zelin, Tong (Acta Bioethica, 2025)
This study examines the impact of socio-cultural factors and informal business networks on ethical marketing practices in the biomedical industry of Gilgit-Baltistan, Pakistan. Using a qualitative research approach, data were collected through in-depth interviews with 36 respondents, including healthcare providers, biomedical product distributors, and local business stakeholders. Thematic analysis identified six major themes: (1) Trust-Based Marketing & Relationships, (2) Informal Business Networks & Influence, (3) Cultural & Community Influence, (4) Ethical Challenges & Trade-offs, (5) Traditional & Incentive-Driven Marketing, and (6) Regulatory Barriers & Compliance Issues. Findings indicate that trust-based relationships, word-of-mouth referrals, and informal agreements significantly shape marketing strategies, often at the cost of ethical transparency and regulatory compliance. Moreover, cultural expectations and social credibility outweigh formal ethical guidelines, leading to ethical trade-offs and weak policy enforcement. The study highlights the need for context-sensitive ethical marketing frameworks that balance local socio-cultural values with formal regulatory requirements. Strengthening policy interventions, regulatory oversight, and ethical awareness campaigns could help to mitigate the dominance of informal business networks and enhance compliance in biomedical marketing. The findings contribute to the broader discourse on business ethics, marketing regulations, and the role of socio-cultural norms in shaping commercial practices in developing regions.